Levantamento de correlações de solidificação da liga A356 para aplicação em simulação computacional e projetos de rodas automotivas - Santos, Pedro Gabriel Benedito de Oliveira (2024)
Wheels are safety items with high structural demand. AlSi alloys stand out due to their good ratio between density and strength. The use of A356 alloy processed by Low-Pressure Die Casting (LPDC) and T6 heat treatment arises from the need for adequate mechanical properties and ease of cyclic processing on a large scale. The high competitiveness of the sector demands a shorter time-tomarket and better performance. Casting numerical simulations assist in predicting thermal and microstructural parameters resulting from the solidification process of the alloy in metallic molds. Understanding thermal parameters is essential for predicting either the phase morphologies or the dendritic length-scale of the casting, as these characteristics have a direct impact on the alloy’s strength. This Master’s work aims to define theoretical equations for application in commercial casting software, to predict the tensile properties of cast and heat-treated wheels. For this purpose, directional solidification (DS) experiments were conducted with A356 alloy to determine equations relating solidification time and cooling rate along the cast part. The part generated by DS was subsequently divided into sections – treated and untreated. Each half was examined in tensile tests, and the secondary dendrite arm spacing (SDAS or λ2) was determined using an optical microscope. This allowed the development of experimental equations relating SDAS to solidification time and tensile properties to SDAS. Finally, simulation with the equations was validated using real tensile test data of wheels before and after T6 treatment. This test involved two methods of correlating tensile properties with SDAS: Hall-Petch (HP) type and Ludvig model (LM). The HP model more accurately represented the tensile strength data from various regions of the wheels, with an average error of approximately 5.6% for tensile strength.